2020
DOI: 10.1021/jacs.0c10884
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogenation of Thioesters, Thiocarbamates, and Thioamides

Abstract: Direct hydrogenation of thioesters with H2 provides a facile and waste-free method to access alcohols and thiols. However, no report of this reaction is documented, possibly because of the incompatibility of the generated thiol with typical hydrogenation catalysts. Here, we report an efficient and selective hydrogenation of thioesters. The reaction is catalyzed by an acridine-based ruthenium complex without additives. Various thioesters were fully hydrogenated to the corresponding alcohols and thiols with exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…It is instructive to first briefly reiterate several critical mechanistic observations in our initial reports. 14 , 16 The key findings are summarized as follows: Ruthenium acridine-9H pincer complex, Ru-1 reacts with hexanethiol (HexSH) at room temperature to afford Acr PNP iPr *RuH(HexSH)(CO) ( Ru-2 ) and Acr PNP iPr *RuSHex(CO) ( Ru-3 ), which upon heating transforms exclusively to Ru-3 with the elimination of H 2 in nearly complete conversion. Under H 2 pressure, an equilibrium with Ru-2 is observable ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is instructive to first briefly reiterate several critical mechanistic observations in our initial reports. 14 , 16 The key findings are summarized as follows: Ruthenium acridine-9H pincer complex, Ru-1 reacts with hexanethiol (HexSH) at room temperature to afford Acr PNP iPr *RuH(HexSH)(CO) ( Ru-2 ) and Acr PNP iPr *RuSHex(CO) ( Ru-3 ), which upon heating transforms exclusively to Ru-3 with the elimination of H 2 in nearly complete conversion. Under H 2 pressure, an equilibrium with Ru-2 is observable ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
“… 22 Initial pressures of H 2 gas in the system above 1.4 bar essentially prevent the dehydrogenative process, whereas when the reaction was performed in an open system, essentially quantitative yield was achieved ( Table 2 , Entry 6).With respect to the reverse reaction, and in accord with these findings, we reported that only 3 bar of H 2 is required to promote thioester hydrogenation stoichiometrically, and as low as 10 bar of H 2 is suitable for the catalytic hydrogenation. 16 Clearly, the overall equilibrium is governed by the hydrogen pressure in the system.…”
Section: Resultsmentioning
confidence: 99%
“…No detectable amounts of Ru-1 or Ru-2 were found in solution, but a new ruthenium complex was observed as the predominant species. This complex could be obtained independently by mixing Ru-1 with NACET, 36,[64][65][66] and was characterized by NMR spectroscopy as the ruthenium-hydrido-thiol complex Ru-4 (Figure 3c). When the solution containing this complex was heated at 100 °C for 10 min, a Ru-thiolate complex formed, accompanied by the release of H2 gas.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31] However, in transition metal catalysis, this strong affinity of thiol(ate)s is usually problematic, since it can easily poison the catalysts by blocking their metal centers. [32][33][34][35][36][37][38] For example, this poisoning effect of thiols could quench the active Au sites dispersion in supported Au nanoparticles used for benzyl alcohol oxidation. 38 Nevertheless, coordinated thiols can dissociate from metal centers and be displaced by other ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Thioester, thiocarbamate, thioamide hydrogenation: In 2020 our group also reported the reverse reaction, namely thioester hydrogenation to alcohols and thiols under low H 2 pressure, catalysed by the acridine-based dearomatized complexes. 96 Under H 2 pressure, the equilibrium between the thiol and thiolate complex becomes tilted toward the formation of thiol, which allows the reaction to proceed in the opposite direction (Figure 32a). Thioester reduction, while readily achieved in biological systems by the thioester reductase enzyme under benign conditions, had been synthetically limited prior to this study to the use of stoichiometric reducing agents.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%